Studi percobaan pembiakan zooplankton jenis Cladocera (Macrothrix sp) secara eksitu: Test Study of Culturing a Type of Zooplankton: Cladocera (Macrothrix sp) using Ex-situ Method - Hamdhani Hamdhani (Fakultas Perikanan dan Ilmu Kelautan, Universitas Mulawarman, 2022)
Zooplankton pays important role in food chain system within fresh water ecosystem. In the trophic level it acts as bridging energy from phytoplankton to fish juvenile. Meanwhile research on this plankton is considerably lacking. This study is aimed to test culturing cladocera in the laboratory. Cladocera and phytoplankton were collected from Lutan Lake-Palangkaraya and the transported to the laboratory. Three fish water tank were used to culture cladocera for 5-week testing. The results indicate that there was fluctuation in average number of individual during culturing period. However the trendlines show increase in average number of individual, this increase was relatively consistent with the increase in average number of phytoplankton. Two week culturing period was identified as the most optimal period for culturing cladocera.